Expression of Estrogen Receptor β in Hypothalamic Stem Cells - Zhen, He; Li, Cui; Sherry, A. Ferguson; Merle, G. Paule (Journal of Evolving Stem Cell Research, 2017)
Neural stem cell activity at least partially accounts for the postweaning development of the sexually dimorphic nucleus of the preoptic area (SDN-POA) and estrogen selectively mobilizes neural stem cells in the 3rd ventricle stem cell niche (3VSCN). Here, we examined the expression of estrogen receptor β (ERβ) in the SDN-POA and the 3VSCN. A subset of cells within the SDN-POA--delineated with or without calbindin D28K (CB28)-immunoreactivity (ir)--exhibited ERβ-ir. The ependymal cells that expressed nestin within the 3VSCN also expressed ERβ. Interestingly, a few proliferating (Ki67 positive) cells within the 3VSCN and the hypothalamic parenchyma, including the SDN-POA, displayed ERβ-ir. In parallel, a subset of cells in the subventricular zone was double-labeled with nestin and ERβ or Ki67 and ERβ while the subgranular zone exhibited few such double-labeled cells. ERβ is expressed in hypothalamic stem cells that may regulate cell regenerative cycles.
Keywords: Estrogen receptor beta; immunoreactivity; Ki67; nestin; 3rd ventricle stem cell niche; sexually dimorphic nucleus.